1994
DOI: 10.1515/znc-1994-1-210
|View full text |Cite
|
Sign up to set email alerts
|

Induced Accumulation and Potential Antioxidative Function of Rutin in Two Cultivars of Nicotiana tabacum L.

Abstract: The rutin (quercetin-3-rhamnosyl-glucoside) content of two tobacco cultivars (Nicotiana tabacum L.) which differ in their ozone-sensitivity was assayed after exposure to various rutininducing stimuli. In the growth-chamber, UV radiation in combination with white light led to the accumulation of similar amounts of rutin in both cultivars. Treatment with radical producing agents (tert-butylhydroperoxide and paraquat) also led to rutin accumulation. In this case, the rutin content was higher in the tolerant culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…27−30 It has been reported that flavonol glucosides of quercetin and kaempferol have multiple functional roles in plant responses to abiotic stress, 31 including water deficit stress in response to UV-B radiation, and may contribute to ozone tolerance. 32,33 Moreover, studies with strawberries grown under UV-blocking film exhibited lower contenst of quercetin 3glucuronide and kaempferol 3-glucoside than those grown in the open field. 34 In accordance with our results, the increase in flavonols in response to 20% CO 2 treatment may reflect a CO 2 tolerance strategy, and so no such accumulation was observed in 40% CO 2 -treated fruit.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27−30 It has been reported that flavonol glucosides of quercetin and kaempferol have multiple functional roles in plant responses to abiotic stress, 31 including water deficit stress in response to UV-B radiation, and may contribute to ozone tolerance. 32,33 Moreover, studies with strawberries grown under UV-blocking film exhibited lower contenst of quercetin 3glucuronide and kaempferol 3-glucoside than those grown in the open field. 34 In accordance with our results, the increase in flavonols in response to 20% CO 2 treatment may reflect a CO 2 tolerance strategy, and so no such accumulation was observed in 40% CO 2 -treated fruit.…”
Section: ■ Discussionmentioning
confidence: 99%
“…On the contrary, no increase in kaempferol 3-glucuronide and quercetin 3-glucoronide levels occurred in fruit treated with 40% CO 2 , although these levels did not differ from those found at time of harvest. It is well-known that the amounts of flavonols vary substantially among the different strawberry cultivars, although, in general, quercetin and kaempferol are the major flavonols and occur as 3-glucosides and 3-glucuronides. It has been reported that flavonol glucosides of quercetin and kaempferol have multiple functional roles in plant responses to abiotic stress, including water deficit stress in response to UV-B radiation, and may contribute to ozone tolerance. , Moreover, studies with strawberries grown under UV-blocking film exhibited lower contenst of quercetin 3-glucuronide and kaempferol 3-glucoside than those grown in the open field . In accordance with our results, the increase in flavonols in response to 20% CO 2 treatment may reflect a CO 2 tolerance strategy, and so no such accumulation was observed in 40% CO 2 -treated fruit.…”
Section: Discussionmentioning
confidence: 99%
“…A highly active rhamnosyltransferase must be present to transfer rhamnose onto the flavonoid glucosides to produce the rutinosides. The production of rutin (quercetin rutinoside) by N. tabacum has been shown to be affected by light quality (Fu et al, 2016), radical producing agents (Steger-Hartmann et al, 1994) and the transcription factor gene NtFLS2 (Shi et al, 2017). However, the level of rutin was unchanged after methyl jasmonate treatment of N. attenuata (Kein€ anen et al, 2001).…”
Section: Formation Of Increased Level Of Rutinosides Upon Agroinfiltrmentioning
confidence: 99%